Pluralism and Religious Harmony in Religious Elites Perspectives in Malang City - Umi Sumbulah (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This study aims to understand the religious elite view of pluralism and religious harmony in Malang. The study was focused on the meaning of pluralism and religious harmony, efforts and things that support and hinder the realization of religious harmony. Empirical research data with qualitative-phenomenological approach was collected through interviews and documentation. The results show: first, the meaning of religious pluralism for the religious elites is very varied, which is the same as tolerance, mutual respect, the goal of all religions are the same, and recognize the fact that there are many religions in this world. Second, religiousharmony have meaning as a condition where there is no oppression and domination of one religion over other religions, awakening a deep awareness of diversity, respect for human rights, and the willingness to spread kindness and love for fellow human beings. Third, religious harmony can be achieved through internal efforts to strengthen the faith of each and build awareness to develop a positive attitude towards other religions. In external efforts to create harmony done through emancipatory dialogue and cooperation to resolve humanitarian issues. Fourth, positive attitude that supports the creation of harmony of religions is the willingness and awareness to understand each other and share experiences. Egoism, truth claims, fanaticism, and exclusivism is a negative attitude and expression recognized by the religious elite can interfere with the establishment of inter-religious harmony.